2020
DOI: 10.1016/j.isci.2020.101758
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective on Biofuels Use and CCS for GHG Mitigation in the Marine Sector

Abstract: Summary The greenhouse gas (GHG) emissions of the marine sector were around 2.6% of world GHG emissions in 2015 and are expected to increase 50%–250% to 2050 under a “business as usual” scenario, making the decarbonization of this fossil fuel-intensive sector an urgent priority. Biofuels, which come in various forms, are one of the most promising options to replace existing marine fuels for accomplishing this in the short to medium term. Some unique challenges, however, impede biofuels penetration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 119 publications
(197 reference statements)
0
24
0
Order By: Relevance
“…Membrane separation is a less mature technology, but has potentially lower capital and operating costs associated, and it presents a small footprint, with no hazardous emissions. CO 2 scrubbing is a more mature technology, already implemented for flue gas emissions at power plants [13] . After removing the pollutants, the remaining CO 2 could be stored aboard using compression or liquefaction.…”
Section: How Could the Solution Be Implemented?mentioning
confidence: 99%
“…Membrane separation is a less mature technology, but has potentially lower capital and operating costs associated, and it presents a small footprint, with no hazardous emissions. CO 2 scrubbing is a more mature technology, already implemented for flue gas emissions at power plants [13] . After removing the pollutants, the remaining CO 2 could be stored aboard using compression or liquefaction.…”
Section: How Could the Solution Be Implemented?mentioning
confidence: 99%
“…At the same time, greater breakthroughs have been made in key technical levels [47]. CCS technical level has been greatly improved and is widely used in the thermal power industry [48][49][50][51]. In addition to technology, national policies are also more effective.…”
Section: Scenario Analysis and Dynamic Simulationmentioning
confidence: 99%
“…Another advantage of biofuels for marine applications is that they can be used as a ready, drop-in fuel with minor changes required for the existing ship engines and infrastructure such as bunkering vessels. Several biofuels produced via various pathways, such as fermentation, pyrolysis, , Fischer–Tropsch (FT) synthesis, and hydrothermal liquefaction (HTL), , are being investigated for their compatibility with the current ship engines and infrastructures. Furthermore, BP has partnered with Maersk Tankers to test the biofuel derived from 30% fatty acid methyl esters blended with very low sulfur fuel oil (VLSFO) on the vessels sailing from Rotterdam to West Africa in 2021 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies reported on the feedstock availability, economic viability, and fuel compatibility of different biofuel options for marine applications. For example, Mukherjee et al ( 10 ) analyzed and compared the performance and viability of biomass gasification, FT synthesis, hydrotreatment of yellow grease, and woody biomass fast pyrolysis (FP), as assessed by techno-economic analysis (TEA) and life cycle analysis. Along the same lines, comprehensive investigations were performed by the International Energy Agency (IEA) and by the Netherlands Maritime Knowledge Centre in 2017.…”
Section: Introductionmentioning
confidence: 99%